The Influence of Brand Image, Halal Label, and Price on the Purchasing Decision of Wardah Cosmetic Products among Female Students of the Management Study Program, University of North Sumatra - Dea Arantika; Hesti Sabrina (SAJMR : Southeast Asian Journal of Management and Research, 2026)
This study aims to analyze the effect of brand image, halal label, and price on purchasing decisions of Wardah cosmetic products among female students of the Management Study Program at the University of North Sumatra. The research uses a quantitative approach. The population consists of 395 female students from the 2022–2024 cohorts, with a sample of 80 respondents selected using the Slovin formula. Data were analyzed using multiple linear regression with SPSS Statistics software. The results show that brand image (X1) has a positive but insignificant effect on purchasing decisions (Y), as indicated by a significance value of 0.238 > 0.05 and a t-value of 1.190 < 1.991. The halal label (X2) has a positive and significant effect on purchasing decisions, with a significance value of 0.000 < 0.05 and a t-value~ of 5.124 > 1.991. Price (X3) also has a positive and significant effect on purchasing decisions, shown by a significance value of 0.000 < 0.05 and a t-value~ of 3.326 > 1.991. Furthermore, the F-test result shows a significance value of 0.000 < 0.05, indicating that brand image, halal label, and price simultaneously have a positive and significant effect on purchasing decisions of Wardah cosmetic products.